Curating Within Musical Ensembles. Issue 1 (1st March 2022) - Scales, Barbara
Abstract : The central question for curating innovative performances by ensembles, which connect to their moment in time and to their audiences, is deciding what to play, and why. What repertoire shall we play? Or perhaps, what shall we arrange? What should we learn and practice, and what should we commission? And underlying these questions is the wonder-filled query: Why? What is the magical combination that informs these choices? I explored these central questions via a two-hour virtual conversation with leaders of three very different ensembles. My starting point for this exploration is that music ensemble leaders are involved in a complex process of making choices in relation to the intention of their ensemble and the time and place of the performance. Even if they do not already use the word, I suggest that curating is what these ensembles are doing. In order to grasp the nature of curation, we can learn a great deal from the process as it develops within an ensemble.